2018
DOI: 10.1177/1360780418761207
|View full text |Cite
|
Sign up to set email alerts
|

International Students’ Perceptions and Experiences of British Drinking Cultures

Abstract: While the increased scale and importance of international students to the UK Higher Education sector is now well established, little is known about the ways in which students from non-UK countries experience and interact with the heavy drinking culture that predominates on and near many British universities. Drawing on qualitative interviews, this article analyses the perceptions, attitudes and experiences of British drinking cultures held by international students studying on postgraduate courses at a UK univ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…Other studies have reported the socialisation constraints experienced by students from some cultural backgrounds, not only among those from a Muslim background, in relation to how and where alcohol is served, consumed or is simply available [ 5 , 37 ]. This study deepens knowledge about international students’ experiences, outlining four categories of alcohol consumption as identified above (Drink heavily; Drink moderately; Don’t drink; Don’t attend events with drink).…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have reported the socialisation constraints experienced by students from some cultural backgrounds, not only among those from a Muslim background, in relation to how and where alcohol is served, consumed or is simply available [ 5 , 37 ]. This study deepens knowledge about international students’ experiences, outlining four categories of alcohol consumption as identified above (Drink heavily; Drink moderately; Don’t drink; Don’t attend events with drink).…”
Section: Discussionmentioning
confidence: 99%
“…The role played by alcohol consumption in facilitating sociability and the formation and maintenance of friendships and other intimate social relationships is well established in academic literature (See Thurnell-Read 2016). Pub based drinking has long been the central leisure activity in many communities (Mass Observation 1943) and pubs remain widely recognized as unique social spaces that draw people together in public settings (Markham 2013;Thurnell-Read et al 2018). Pubs are seen as places where informal social interaction is encouraged (Dunbar 2016) and where at other times strictly maintained codes of conduct and comportment can be relaxed, making conversation between strangers and casual acquaintances possible (Fox 2005).…”
Section: Getting Social Down the Local?mentioning
confidence: 99%
“…Whilst the research team did try to recruit students from a wide range of backgrounds, and all recruitment materials specified that non-drinkers were encouraged to take part, the majority of the students that were recruited were White British. For example, other studies have demonstrated how other groups of students, such as international students ( Thurnell-Read, Brown, & Long, 2018 ) have very different experiences of alcohol consumption and this study is not representative of those that do not fit the mainstream stereotype of students in the UK. Furthermore, the focus groups and paired interviews were carried out with existing peer groups.…”
Section: Methodsmentioning
confidence: 91%